CALCINEURIN INHIBITOR-INDUCED RENAL ALLOGRAFT NEPHROTOXICITY - Krejci, Karel; Tichy, Tomas; Bachleda, Petr; Zadrazil, Josef (Biomedical papers, 2010)
Background: The introduction of the calcineurin inhibitors (CI) cyclosporine and tacrolimus into immunosuppressive protocols initiated a new era in organ transplantation with excellent short-term graft survival. Nevertheless, the chronic nephrotoxicity of these drugs represents a significant adverse factor limiting their long-term use. Patients treated with a CI can be at risk for developing renal failure and this problem is especially pronounced in patients after renal transplantation.Methods and Results: In a review paper we summarize the clinical aspects, histological manifestations and pitfalls of diagnostics of acute and chronic CI nephrotoxicity in patients after kidney transplantation. We look in detail at the disputed relationship between blood concentrations of cyclosporine and tacrolimus and histological manifestation of toxicity and summarize data showing that for toxic effects, local renal exposure to CI and their metabolites can play a more significant role than systemic exposure. We also include recent views on the pathophysiologic and molecular mechanisms underlying these changes; factors influencing local susceptibility to CI nephrotoxicity are discussed, including variability of expression and activity of P-glycoprotein and cytochrome P450. Last but not least we summarize our own experience with clinically manifest and subclinical forms of nephrotoxicity and their impact on the progression of chronic graft changes.Conclusions: Owing to their unique effects, CI remain the cornerstone of most immunosuppressive protocols for renal transplantation. Together with optimization of local kidney exposure to CI and their metabolites, efforts to reduce systemic levels as much as possible are the most important preventive measure for reducing toxic renal graft damage.
Keywords: Calcineurin inhibitors/Cyclosporine and tacrolimus/Renal allograft/Nephrotoxicity/Risk factors/Prevention